2017
DOI: 10.1021/acs.jpca.7b01067
|View full text |Cite
|
Sign up to set email alerts
|

Water Solvent Effect on Theoretical Evaluation of 1H NMR Chemical Shifts: o-Methyl-Inositol Isomer

Abstract: In this paper, density functional theory calculations of nuclear magnetic resonance (NMR) chemical shifts for l-quebrachitol isomer, previously studied in our group, are reported with the aim of investigating in more detail the water solvent effect on the prediction of H NMR spectra. In order to include explicit water molecules, 20 water-l-quebrachitol configurations obtained from Monte Carlo simulation were selected to perform geometry optimizations using the effective fragment potential method encompassing 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
4
13
0
Order By: Relevance
“…The agreement with experimental 1 H NMR signals for rutin lateral chain protons could be improved using explicit solvent molecules as reported in Ref. for l ‐quebrachitol, where 50 water molecules surrounded the solute embedded in a continuum model (PCM). Such approach involves a high computational demand and according to the results from Ref.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The agreement with experimental 1 H NMR signals for rutin lateral chain protons could be improved using explicit solvent molecules as reported in Ref. for l ‐quebrachitol, where 50 water molecules surrounded the solute embedded in a continuum model (PCM). Such approach involves a high computational demand and according to the results from Ref.…”
Section: Resultssupporting
confidence: 77%
“…Such approach involves a high computational demand and according to the results from Ref. is not strictly necessary. It was found that the PCM model provides a very reasonable account of the solvent effect on the calculation of NMR spectra for organic molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The agreement with experimental 1 H NMR spectrum measured in solution can be improved with the use of explicit solvent molecules in the B3LYP NMR calculation, as reported in Ref. , where 50 water solvent molecules surrounding the l ‐quebrachitol solute was used in conjunction with the PCM model to better describe the solvent effect. Such approach precisely represents solute‐solvent interactions, however involves a high computational demand.…”
Section: Discussionmentioning
confidence: 56%
“…From the results reported in Ref. , it can be seen that such more elaborate procedure is not strictly necessary, with the PCM continuum model providing a satisfactory description of the solvent effect on the calculation of NMR spectra for structural determination of organic molecules.…”
Section: Discussionmentioning
confidence: 99%